2019
DOI: 10.29052/2412-3188.v6.i1.2019.15-22
|View full text |Cite
|
Sign up to set email alerts
|

Computer vision syndrome: prevalence and predictors among students

Abstract: Background: Globally around 60 million people are suffering from Computer vision syndrome (CVS). A well-known eye and vision-related problem resulting from prolonged computer, tablet, e-reader and cell phone use. Viewing a digital screen often increases the visual load therefore the aim of this study was to explore the prevalence of CVS among students. Methodology: This cross-sectional study was conducted from 1st September 2018 to 31st May 2019 on a sample of 320 students from diverse physiotherapy institutes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…A total of 45 cross-sectional and 4 case control studies were included in this systematic review and meta-analysis: four studies in Saudi Arabia, 3942 four studies in Pakistan, 4346 three studies in Spain, 4749 three studies in Ghana, 5052 seven studies in Ethiopia, 5358 five studies in Egypt, 11,5962 two studies in Nigeria, 63,64 one study in Jordan, 65 two studies in China, 66,67 one study in Iran, 68 one study in Nepal, 69 eight studies in India, 18,7076 one study in South Korea, 77 one study in Seri Lanka, 78 one study in Italy, 29 two studies in Brazil, 79,80 one study in Beirut, 81 one study in Japan, 82 and one study in Thailand. 83 A total of 23,399 sample sizes were included.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 45 cross-sectional and 4 case control studies were included in this systematic review and meta-analysis: four studies in Saudi Arabia, 3942 four studies in Pakistan, 4346 three studies in Spain, 4749 three studies in Ghana, 5052 seven studies in Ethiopia, 5358 five studies in Egypt, 11,5962 two studies in Nigeria, 63,64 one study in Jordan, 65 two studies in China, 66,67 one study in Iran, 68 one study in Nepal, 69 eight studies in India, 18,7076 one study in South Korea, 77 one study in Seri Lanka, 78 one study in Italy, 29 two studies in Brazil, 79,80 one study in Beirut, 81 one study in Japan, 82 and one study in Thailand. 83 A total of 23,399 sample sizes were included.…”
Section: Resultsmentioning
confidence: 99%
“…According to our results, the top five most debilitating symptoms of CVS were dryness (29.7%), headache (26.9%), worsening sight (26.6%), burning (17%), and itching (16.5%), while double vision represented the least symptom. Studies suggest that headache was the most prominent symptom complained by the students [ 3 - 4 , 6 , 8 , 9 , 11 , 12 ]. Contradicting these reports, Abudawood et al revealed that excessive tearing was the students' most common symptom, followed by shoulder and back pain [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 45 cross-sectional studies with 17,526 sample sizes were included in this systematic review and meta-analysis: four studies in Saudi Arabia 40 43 , two studies in Nigeria 44 , 45 , three studies in Ghana 46 – 48 , four studies in Pakistan 49 – 52 , three studies in Spain 53 55 , seven studies in Ethiopia 56 62 , one study in Jordan 63 , two studies in China 64 , 65 , one study in Iran 66 , three studies in Egypt 67 – 69 , eight studies in India 18 , 70 76 , one study in Nepal 77 , one study in Sri Lanka 29 , two studies in Brazil 78 , 79 , one study in Beirut 80 , one study in Japan 81 , and one study in Thailand 82 . The sample size ranged from 74 in China 64 to 2210 in Sri Lanka 29 (Table 1 ).…”
Section: Methodsmentioning
confidence: 99%